Analisis Desain Cover Buku Anak Ayo Sekolah Lukisan Aini - Galingging, Rumbel (Magenta | Official Journal STMK Trisakti, 2020)
The scope of education itself is recognizing letters to being able to read and write, recognizing numbers to counting correctly, and recognizing colors and shapes in order to get to know the surrounding environment. This should have been learned from an early age or kindergarten age, because at that time children easily absorb the information given to them. It is for this reason that children must be facilitated with things that can facilitate their learning process, one of which is by providing books. To make it easier and to make children interested in understanding the contents of the reading, books are made with attractive illustrations and colors for children, so that they are interested in reading and understanding the contents of the book. One of the media for channeling education is through picture story books. Picture story books are one way of shaping children’s personalities, picture story books also provide many other benefits such as rhythm, rhymes, pictures that can stimulate language development and listening skills for children. ABSTRAK Ruang lingkup pendidikan itu sendiri adalah mengenal huruf hingga dapat membaca dan menulis, mengenal angka hingga dapat berhitung dengan benar, serta mengenal warna dan bentuk agar dapat mengenal lingkungan sekitarnya. Hal ini seharusnya sudah dipelajari sejak usia dini atau usia taman kanak-kanak, karena pada masa itu anak mudah menyerap informasi yang diberikan kepada mereka, karena alasan inilah anak harus difasilitasi dengan hal-hal yang dapat mempermudah proses pembelajaran mereka, salah satunya adalah dengan menyediakan buku. Untuk mempermudah dan membuat anak tertarik dalam memahami isi bacaan, maka buku dibuat dengan ilustrasi dan warna yang menarik untuk anak, sehingga mereka tertarik untuk membaca dan memahami isi buku tersebut. Salah satu media untuk menyalurkan pendidikan adalah melalui buku cerita bergambar. Buku cerita bergambar merupakan salah satu cara membentuk kepribadian anak, buku cerita bergambar juga memberikan banyak manfaat lainnya seperti, irama, sajak, gambar yang dapat merangsang pengembangan bahasa dan ketrampilan mendengar bagi anak-anak.